Ultrasound may promote fracture healing but this does not necessarily accelerate return of function - O'Herlihy, L.; Elkins, M. R. (British Journal of Sports Medicine, 2013)
Bone fractures are common, affecting about six million people in North America annually with associated pain, loss of function and socioeconomic expenditure. Although spontaneous union of uncomplicated fractures is typically described as occurring within 6-8 weeks, the duration of fracture healing varies by the site and type of fracture. Bone mineral density, smoking and underlying disease can further affect the healing time. While most fractures unite spontaneously, 5-10% of long-bone fractures having delayed healing or do not unite, although again the characteristics of the fracture and the patient can influence this. Delayed and non-union exacerbate the morbidity, dependence and lost productivity associated with fractures. Regardless of the predicted healing time for individual patients, stimulation of bone formation at the fracture site may reduce the healing time and the risk of non-union. Furthermore, it could reduce the total duration for which distraction osteogenesis needs to be performed. Many interventions have been proposed as potential stimulators of bone formation including medication, growth hormone, electric currents, magnetic fields, shockwave therapy and ultrasound. Ultrasound might induce fracture healing by applying mechanical forces at the fracture site.